Estratégia de uso de água salobra na irrigação de cana-de-açúcar - CARVALHO, Pedro Henrique Máximo de Souza (2022)
The sugarcane production system in Brazil is responsible for generating employment and income in the Brazilian countryside and, in Pernambuco, a large part of its production takes place in coastal areas. These areas, as used in irrigation, may have high levels of salts, due to marine invasion, which, when used without proper management, can facilitate salinization of soils and, consequently, reduce that of plants. In this way, knowledge and strategies of use in agriculture are necessary, as is the case of leaching water, which provides the leaching of excess salts in the root zone. Thus, the objective of this work was to evaluate the effects of the use of brackish water and leaching fractions on the performance of sugarcane, in the third ratoon. Thus, the objective of this work was to evaluate the effects of the use of brackish water and leaching fractions on the performance of sugarcane, in third ratoon. The study was carried out at the Universidade Federal Rural de Pernambuco, in Recife, using drainage lysimeters. The RB92579 variety was evaluated, in a third ratoon, in a completely randomized design, with five irrigation water salinity levels (ECa: 0.5; 2.0; 3.5; 5.0; 6.5 dS m-1 ) and two leaching fractions (0 and 0.17). Saline levels were obtained by adding NaCl and CaCl2, in a 1:1 molar ratio. Between 60 days after cutting (DAC) and 150 DAC were evaluated: stem height, stem diameter, leaf area, number of tillers and leaf area index. At 145 DAC, evaluations of: photosynthesis, stomatal conductance and transpiration occurred. The use of leaching fraction 0.17 proved to be effective in mitigating the effects of stress caused by NaCl and CaCl2, resulting in greater biometric development and providing an increase in photosynthetic rate, stomatal conductance and foliar transpiration of plants. The leaching fraction technique was shown to be a viable method to control salinity when using lower quality water. Thus, this technique can be used in sugarcane fields that have irrigation conditions with brackish water.